On the role of the indenyl effect in controlling intramolecular hydride transfer in iron carbonyl complexes - Ahmed, H; McGrady, J (2008)
Density functional theory reveals multiple pathways for intramolecular hydride transfer in the cyclopentadienyl and indenyl species (η 5-C 5H 5)Fe(CO) 3H and (η 5-C 9H 7)Fe(CO) 3H. The ability of the indenyl ligand to undergo facile η 5- to η 3-'ring slippage' stabilises the isomer where the hydride is bonded directly to the metal, which opens up a low-energy pathway for hydride transfer from CO to metal. © 2008 Elsevier B.V. All rights reserved.